Classifying Organizational Structures on Targets in the Cooperative Target Observation - Silva, Thayanne; Araújo, Matheus; F. Junior, Raimundo; Costa, Leonardo; Andrade, João; Campos, Gustavo (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2020)
This paper proposes an approach to classify the organizational structure of a group of moving target agents that are continuously monitored by a smaller group of moving observer agents. The approach considers that the group of target agents can organize themselves according to eight different paradigms. The agents communicate through the exchange of messages whose contents are speech-act performative. We evaluate the approach considering seven techniques to solve the problem of classifying the group of target agents' organizational structure. The results show that the approach is promising, as it obtained a good performance, measured during experiments using agent-based simulations.